MODERASI BERAGAMA DAN LITERASI DIGITAL - Rizal, Derry Ahmad; Vella, Nurul Khorina Seci (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2024)
This study focuses on digital literacy as an approach to critically analyzing media content, with particular attention to information that promotes the values of religious moderation. The primary issue addressed is how digital literacy managed by the Pastoral Development Unit (UPP) of the Archdiocese of Semarang, through the social media account @komsos_kas, contributes to fostering religious moderation. The study aims to identify strategies for disseminating positive values through social media. The research employs a descriptive qualitative method with a literature review approach. Data were obtained through content analysis of the Instagram account @komsos_kas, which has over 17,000 followers, as well as additional content from YouTube and the official website of the Archdiocese. The data analysis technique involves thematic analysis of content related to religious moderation. The findings reveal that social media serves as a strategic platform for conveying the values of religious moderation to a broader audience, particularly millennials. The content uploaded includes messages of interfaith tolerance, reflections on solidarity, and rejection of radicalism. Although social media poses potential adverse impacts, the @komsos_kas account successfully leverages digital platforms to promote inclusive and positive narratives. In conclusion, the digital literacy initiatives implemented by the Pastoral Development Unit of the Archdiocese of Semarang play a crucial role in encouraging interfaith dialogue, fostering social harmony, and advancing religious moderation.